Uszkodzenia drzewostanu w zależności od metody pozyskiwania drewna ze zrywką ciągnikiem - Karaszewski, Zbigniew; Bembenek, Mariusz; Dobek, Anita; Giefing, Dieter; Mederski, Piotr; Stergiadou, Anastasia (Leśne Prace Badawcze, 2013)
Damage to the remaining stand is an unavoidable consequence of thinning operations. The different machines used for timber extraction differ in the level of damage of trees they cause, mainly through wounds to the bark and cambium which can make a substantial impact on the remaining trees. Three different methods of timber harvesting with a chainsaw were analysed: the short wood system (SWS), the long wood system (LWS) and the full tree system (FTS) in which an agricultural tractor is used for timber extracting. All systems were analysed in stands containing three different age classes: 2nd (21-40 years), 3rd (41-60 years) and 4th (61-80 years). The level of damage to the remaining stand was assessed considering the percentage of trees exhibiting wounds (scratched bark and/or damage to the cambium) to calculate an index of stand damage (WDI) which incorporated the volume of harvested timber per hectare. The SWS produced the lowest damage to trees in stands of all age classes: average 5%, with the less damage in the oldest stand. After using the LWS 9% of trees were wounded; in this method there was no statistical difference in frequency of wounding across all the analysed stands. The highest level of damage was incurred after the FTS, causing 11% of trees to be injured. In stands of the 2nd age class, the method of timber harvesting had no statistically significant effect on the amount of wounding endured. The WDI was lowest in SWS: 0.08, higher in LWS: 0.15 and the highest, 0.23, when FTS was applied.